THE EFFECT OF FINANCIAL LITERACY AND SELF-CONTROL ON THE CONSUMPTIVE BEHAVIOR OF STATE SENIOR HIGH SCHOOL STUDENTS IN EAST JAKARTA - Aisyah Dzakiyyah; Ari Saptono; Aditya Pratama (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This research with a quantitative approach aims to describe the direct and indirect effects of financial literacy on self-control and consumptive behavior, as well as the role of self-control as a mediating variable between the influence of financial literacy and consumptive behavior. The population in this study were SMA Negeri students in East Jakarta, with a total of 285 students being the sample, which was determined by a proportionate random sampling technique. Data was obtained using a questionnaire distributed through Google Form, then analyzed using path analysis with the help of IBM SPSS Version 25 software. The results showed that: (1) There is a direct influence of financial literacy on consumptive behavior; (2) There is a direct influence of self-control on consumptive behavior; (3) There is a direct influence of financial literacy on self-control; and (4) Self-control is able to mediate the effect of financial literacy on the consumptive behavior of State Senior High School students in East Jakarta. In order to reduce consumptive behavior, the school can create activities that can help students improve their financial literacy and self-control. And for further researchers, it is hoped that they can examine other factors that are thought to influence consumptive behavior.